Measurement of functional recovery in individuals with acute anterior cruciate ligament rupture. Issue 11 (21st October 2005) - Button, K; van Deursen, R; Price, P
Abstract : Objectives: To measure functional recovery following acute anterior cruciate ligament (ACL) rupture using a simple and reliable clinical movement analysis system. Clinic based methods that simultaneously quantify different aspects of movement over a range of activities and model functional recovery will help guide rehabilitation. Methods: A longitudinal study was used to measure gait variables at initial physiotherapy attendance and then at monthly intervals using a digital camcorder and computer for quantitative analysis. Jogging and distance hopping were added during recovery. A sample of 63 ACL deficient subjects entered the study and 48 subjects were measured at least three times. To determine the pattern of recovery, repeated measurements were analysed using a least square fit of the data. Results: Gait variables took between 95 and 130 days post injury to reach the control mean and stabilise shortly after this. Hopping distance for the injured leg took 62 days to recover to within normal limits and 5 months post injury to reach the control mean. Jogging was already within the control limits at 30 days post injury and demonstrated little change with recovery. Conclusions: Functional recovery of multiple variables has been modelled. In the early phase of post injury, gait velocity seems to be the most useful variable to measure improvement. Recovery of more challenging activities appears to take an average of 5 months. Therefore, patients may need to be monitored in physiotherapy until this time and advised not to return to sport until sufficient recovery is demonstrated on activities such as distance hopping.